Working with Large Data: Lessons Learned - Harper, Ellen M; Welton, John M; Baird, Jennifer; Blake, Nancy; Luker, Gayle; Garcia, Amy; Buslon, Dolores; Ritter, Desiree (Nursing economic, 2018)
Nursing researchers and information technology teams worked together with a large and complex data set to measure nursing value.A number of valuable lessons were learned including the importance of partnership, coordination among personnel, complexity of data extraction and transfer, and new analysis techniques.